2010
DOI: 10.1016/j.jcrs.2009.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal corneal ring segment SK implantation for moderate to severe keratoconus

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
64
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 15 publications
11
64
2
Order By: Relevance
“…These results are in agreement with studies of Jadidi et al [30], Jabbarvand et al [33], Alio et al [29] and Sansanayudh et al [32]. The similar results in these studies can be related to similar 6 mm diameter and larger arc of rings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with studies of Jadidi et al [30], Jabbarvand et al [33], Alio et al [29] and Sansanayudh et al [32]. The similar results in these studies can be related to similar 6 mm diameter and larger arc of rings.…”
Section: Discussionsupporting
confidence: 93%
“…Spherical and cylindrical refractive error decreased 1.4 diopter and 1.7 diopter respectively. These results are in line with other studies [8,[30][31][32][33][34][35][36][37][38]. UCVA improved three lines which is compatible with studies of Vega estrad et al [31] and Gharibieh et al [38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with those found in the literature, as most of the studies that have been carried out reported a gain of lines in UDVA. 6,7,10,21,27,28 We observed that the most significant increase in the UDVA was found in patients classified as grade plus, where more than 77% gained 1 or more lines of UDVA. Furthermore, in this group of patients we observed the least number of eyes losing 1 or more lines of UDVA (Tables 6 and 7).…”
Section: In This Study We Evaluated the Outcomes Of Icrsmentioning
confidence: 69%
“…[4][5][6]8,10,21,[25][26][27] In addition, studies that have analyzed the clinical outcomes according to the severity of the disease also reported a significant improvement in patients who suffered from a severe form of keratoconus. 5,21,27 By analyzing the results according to the degree of visual limitation, we found that more than 65% of our patients gain at least 1 line of UDVA after the primary implantation of the ICRS. These results are consistent with those found in the literature, as most of the studies that have been carried out reported a gain of lines in UDVA.…”
Section: In This Study We Evaluated the Outcomes Of Icrsmentioning
confidence: 99%